The Differences between English and Indonesian Lecturer in the Classroom Interaction Based on Sinclair and Coulthard Model - Christine Helena Natalia; Khairunnisa br. Batubara (Randwick International of Education and Linguistics Science Journal, 2020)
This study was about IRF (Initiation-Response-Feedback) analysis on classroom interaction between English and Indonesian lecturer with students. The aimed of this study were to describe the processes of Initiation-Response-Feedback are employed by the English and Indonesian Lecturers with students in classroom interaction based on Sinclair and Coulthard Model. This research used qualitative research. The data of this study were the utterances that expressed by the English and Indonesian lecturer with students in thelearning process. The source of data was English and Indonesian lecturer with the students in STKIP Budidaya Binjai. The data were collected in five ways by Rymes (2009) observing, recording, transcribing, interviewing and analyzing. The data were analyzed based on Sinclair and Coulthard (1975). The result of this study were English subject, the lecturer initiaton was the highest appear in classroom interaction. The students felt enthusiastic in learning it although they had problem in pronounciation and write words but they want to try to do the task given by the lecturer. Lecturer initiation as the highest appear in classroom interaction. The competition as the technique of teaching that lecturer used in this learning process just made one student of each group that become active in share their opinion. The other students felt ashamed to share their opinion because of afraidness to get bad score from the lecturer